Urban Transport : Can Public-Private Partnerships Work? - Engel, Eduardo (World Bank, Washington, DC, 2014)
Cities exist, grow, and prosper because they take advantage of scale economies and specialization wrought by agglomeration. But output growth inevitably stresses transport infrastructure because production requires space and mobility. To prevent congestion from crowding out agglomeration benefits and to expand the supply of urban land, cities must invest in transport infrastructure. Building more infrastructures, especially highways, just fosters sprawl and fails to reduce congestion that people respond to more capacity by driving more and wasting even more time. In this view, a central task for policy makers and planners is to curb the preference for cars. Proponents of this view advocate subsidizing public transportation; enacting taxes and restrictions to raise the costs of owning and driving cars; and establishing zoning regulations to foster compact living, shrink the spatial distribution of activities, and reduce the number of vehicle trips. Yet urban planners often lack formal and real authority to cut through the bureaucratic web of multiple authorities and jurisdictions. Can public-private partnerships (PPPs) deal with these problems better than conventional public provision and ensure proper maintenance, timely expansion, and less congestion?, is discussed in this report.